Proses Komunikasi Dalam Pernikahan Etnis Madura - Nida Fitria Rahmadani; Ghina Farhany (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2019)
One of the ethnic groups in Indonesia who has special uniqueness in terms of their wedding customs is ethnic Madurese. In this study, research to supplement the consultation process of Madura marriage. This study uses qualitative methods by applying the sociocultural tradition. The technique of collecting data used is interview techniques and literature studies. The results of the study showed that the Madurese community still practiced matchmaking. Early marriage and security in the Madurese community begins with matchmaking and occurs due to certain factors such as increasing status and maintaining honor. Because second marriage begins with matchmaking, the communication process is related to the theory of social penetration, while communication between individuals moves to more intimate communication. In this case, non-verbal communication can be found in the wedding attire and tradition. This tradition includes pre-marriage, reception to post-marriage. In the communication process of Madurese ethnic, religious people has a significant role, from being the wedding planner to being the headman, depending on the tradition of the village. Keywords: Madura Ethnicity, Communication Process, Customary Marriage